2008
DOI: 10.1177/1403494808089648
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic correlates of alcohol consumption in the Danish general population

Abstract: With respect to the rest of Europe and North America, Danes consume high levels of alcohol with a large percentage of youth drinking in a binge pattern. Classical socioeconomic factors play a lesser role in determining drinking patterns compared to other Western countries. Longitudinal studies and studies of alcohol-related consequences in the Danish general population should be conducted to better formulate alcohol and public health policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
37
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 16 publications
11
37
1
Order By: Relevance
“…The prevalence of alcohol use is quite varied in different parts of the world. Whilst a study conducted in 20 countries on the African continent identified a prevalence of abstinence above 95% 7 , a population-based study carried out in Denmark found that only 5% of the population abstained, and 14% of men and 9% of women presented problems related to alcohol use 8 . North and East European countries and certain regions in America present the highest levels of alcohol consumption per capita, whilst the lowest levels are observed in Mediterranean countries 9 .…”
Section: Introductionmentioning
confidence: 98%
“…The prevalence of alcohol use is quite varied in different parts of the world. Whilst a study conducted in 20 countries on the African continent identified a prevalence of abstinence above 95% 7 , a population-based study carried out in Denmark found that only 5% of the population abstained, and 14% of men and 9% of women presented problems related to alcohol use 8 . North and East European countries and certain regions in America present the highest levels of alcohol consumption per capita, whilst the lowest levels are observed in Mediterranean countries 9 .…”
Section: Introductionmentioning
confidence: 98%
“…Bloomfield et al (2008) found no significant differences in daily drinking or occasional heavy drinking between different income and educational groups, and explain this with the general acceptance of drinking in Denmark, heavy drinking included.…”
Section: Introductionmentioning
confidence: 62%
“…Denmark, which provides the context of this study, has been shown to have small social status differences in drinking (Bloomfield, Grittner, Rasmussen, & Petersen, 2008;Illemann, Ekholm, Davisen, & Juel, 2012). Bloomfield et al (2008) found no significant differences in daily drinking or occasional heavy drinking between different income and educational groups, and explain this with the general acceptance of drinking in Denmark, heavy drinking included.…”
Section: Introductionmentioning
confidence: 99%
“…Binge drinking among youths is not an exclusively Brazilian phenomenon. In a Danish study involving individuals between 16 and 20 years of age, 74% of males and 59% of females reported having six or more drinks on a single occasion at least once a month 25 . Both the habitual and excessive consumption of alcohol in a short period of time (binge drinking) are essential factors in the analysis of intake amounts.…”
Section: Discussionmentioning
confidence: 99%